Unmaking and remaking everyday life in Diyarbakır: free schools as a decolonizing practice - Dölek, Hazal Ilgaz. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
This thesis is grounded on my fieldwork in Diyarbakır carried out between October 2015 and April 2016. Considering the city as a space of colonial occupation, it examines the broad scale dynamics of the ongoing war as well as the unmakings and remakings of everyday life under siege. It traces the ethnographic sentiments and sensibilities of war and the intimate sites of power production and insurgency. In addition, it also focuses on the mother tongue-based education practices in one of the Free Schools. Free Schools provide a counter space where the already existing colonial ways of learning, knowing and being introduced by the Turkish education system can be decolonized. Therefore, I argue that the alternative philosophy of education they provide to struggle against the assimilationist, capitalist and patriarchal way of life is itself a decolonizing practice.
Keywords: Everyday life -- Diyarbakır (Turkey); Free schools -- Diyarbakır (Turkey)